Simulation of web performance with different IP environment using plone software - Ahmad Fairuz, Ahmad (2014)
The website is one of the applications that are widely used in computer networks to disseminate information to the public. Skills to access or navigate a website depends on the framework and the type of web server used and the use of Internet Protocol be applied. Internet Protocol (IP) is a network protocol that connects the main transmission between networks. Currently, Internet Protocol version 6 (IPv6) is a version of the Internet Protocol (IP) designed to replace and improve the weaknesses in the existing version of the Internet Protocol Version 4 (IPv4). This thesis will analyze the performance of Internet Protocol Version 4 (IPv4) and Internet Protocol Version 6 (IPv6) through access to websites that are developed using Plone technology as its framework (framework) in Dual Stack transition mechanisms. This testing is done in a simulation environment to get more accurate test results. Parameters chosen were response time, the size of bandwidth and the packet size to be used in a comparison test done. Based on the results and analysis in detail, the selection of Internet Protocol (IP) that will best be determined.